Riesgos laborales en los trabajadores de las fábricas de bloque en la ciudad de Zamora. Año 2015 - Lima Sozoranga, Dany Silvania (2016)
The present study was to determine the occupational hazards in the factory workers block in the city of Zamora, the methodology used for this study was cross-sectional, descriptive, field and bibliographical. The sample consisted of 30 persons to which the survey technique was applied to the instrument the questionnaire and the observation guide, the data were tabulated and shown in tables where the sociodemographic characteristics as identified: age with 33.33% 100.00% are male, the 46,66% to secondary level, mixed race ethnicity with 70.00%, 43.33% are construction assistants, among the factors physical risk 100.00% exposed to noise crusher machine and transporting trucks, with respect to solar radiation lack of use of spectacles with 80.00%, vibrations in the failure to use girdles with 90.00%, with respect to chemical risk factors manipulate 100.00% cement and burnt oil used within mechanical risk factors 100.00% inadequate position taken when handling machines and tools. The consequences suffered by the workers which predominates most back pain with 100.00%. Finally we proceeded to develop the intervention plan with training on the subject, demonstration of body mechanics, massage, water compresses applied also took delivery of educational brochures, protective clothing is concluded that there are occupational hazards in factories block and not being supervised by the competent authorities of the General Labour Risk Insurance, will bring permanent and irreversible health consequences for workers. Keywords: Occupational Risks, Workers, Factories